The people project triangle : balancing delivery, business-as-usual, and people's welfare - Copeland, Stuart; Coaton, Andy (Portfolio and project management., 2020)
Driven by rapid external change, the modern corporation is lean and cost conscious. A consequence is an increasingly common project management situation of a medium important, medium complex business change project that cannot justify a full-time team. Consequently, it is resourced by in-house staff working on the project as homework, meaning in addition to their normal responsibilities. The authors term this a composite project. This book postulates that composite projects are increasingly used to meet the demands of rapid business change. However, they are largely unrecognized as a separate organizational category of project, with particular characteristics, management needs, and risks. The People Project Triangle refers to the trade-off between the project, the ongoing business, and the people working in them. When pressure mounts it is often the people who bear the brunt, risking stress and burnout. The authors assert that with better recognition, clearer understanding and appropriate measures, many of the common problems with composite projects can be foreseen and avoided or mitigated.